Grip Force on Steering Wheel as a Measure of Stress - Sahar, Yotam; Elbaum, Tomer; Wagner, Michael; Musicant, Oren; Hirsh, Tehila; Shoval, Shraga (Frontiers in Psychology, 2021)
Driver performance is crucial for road safety. There is a relationship between performance and stress such that too high or too low-stress levels (usually characterized by stressful or careless driving, respectively) impair driving quality. Therefore, monitoring stress levels can improve the overall performance of drivers by providing either an alert or intervention when stress levels are sub-optimal. Commonly used stress measures suffer from several shortcomings, such as time-delays in indication and invasiveness of sensors. Grip force is a relatively new measure that shows promising results in measuring stress during psychomotor tasks. In driving, grip force sensor is noninvasive and transparent to the end user as drivers must continuously grip the steering wheel. The aim of the current research is to examine whether grip force can be used as a useful measure of stress in driving tasks. Twenty-one participants took part in a field experiment in which they were required to brake the vehicle in various intensities. The effects of the braking intensity on grip force, heart rate, and heart rate variability were analyzed. Results indicate a significant correlation between these three parameters. These results provide initial evidence that grip force can be used to measure stress in driving tasks. These findings may have several applications in the field of stress and driving research, as well as in the vehicle safety domain.